(untitled) (Marketing Journal, 2025)
This scientific article explores the scientific and methodological approaches aimed at improving the cargo and passenger transportation system in Uzbekistan. The article examines the efficiency of transport infrastructure, the development of logistics systems, ecological safety, and the integration of digitalization processes into the transport sector. The study analyzes the current state of Uzbekistanʼs transport system, 155 covering rail, road, air, and water transportation. It also examines international practices and provides recommendations to improve the quality of transport services and ensure sustainable development. The findings offer practical recommendations for mode rnizing the transportation system, introducing innovative technologies, and establishing effective management mechanisms.